SYSTEM FOR DETECTION OF NATIONAL HEALTHCARE INSURANCE FRAUD BASED ON COMPUTER APPLICATION - Santoso, Budi; Hendrartini, Julita; Djoko Rianto, Bambang Udji; Trisnantoro, Laksono (Public Health of Indonesia, 2018)
Background: The national healthcare insurance (JKN) has been in deficit since 2014-2016; one of the causes is fraud inpatient hospital service. Objective: This study aimed to analyze the validity, reliability and effectiveness of detection system of national healthcare insurance fraud based on computer application in hospital.Methods: Cross-sectional method was used. Fraud data were collected at one episode in the inpatient JKN participant service.Results: Validity was assessed by Fischer exact test. The interpretation was done by hospital internal verification officer and BPJS Kesehatan verification officer. There were only 2 out of 1.106 services claims were different, resulted in p-value < 0.01. Reliability was assessed using Human Organization Technology Benefit questionnaire filled by admission administrator officer, BPJS Kesehatan officer and hospital internal verification officer; and then analyzed using Stata® software resulting in Cronbach's alpha value of > 0.8. Effectiveness was assessed by reducing potential fraud, conducted by RSUP dr. Soeradji Tirtonegoro from May until July 2017, which on May 2018 there were 8 findings, June 1 finding, and on July 2018 had no finding.Conclusion: System for detection of national healthcare insurance fraud based on computer application is valid, reliable and effective to be implemented in inpatient service in hospital.